Les noms sous-spécifiés anaphoriques résomptifs vs leur équivalent prototypique dans les constructions spécificationnelles attributives : comparaison dans un corpus diversifié en genres - Anaïs Vajnovszki (Studii de Lingvistica, 2022)
Shell nouns (Schmid 2000) are abstract nouns like problem or result, which have the potential to “encapsulate” a portion of text either cataphorically (The problem is that + Propositional content) or anaphorically (Propositional content, this problem…). Since shell nouns operate a discursive reference, they serve as resumption markers, especially when they appear in constructions which create “conceptual anaphoras”, also called “resumptive anaphoras” (Charaudeau and Maingueneau 2002). Among these configurations, we find the construction in which the shell noun, determined by a demonstrative article, starts a sentence (Adler and Legallois 2018). However other variants of this construction exist, for example when the shell noun is not at the beginning of a sentence. Furthermore a prime test for shell-nounhood remains the integration of a noun into specificational attributive constructions, e.g. The problem is that + conjunctive phrase. We will analyse corpus data to identify the common points and the differences between specificational attributive constructions including French shell nouns and anaphorical resumptive constructions involving the same shell nouns.